Electrocatalytic Properties of Pulse-Reverse Electrodeposited Nickel Phosphide for Hydrogen Evolution Reaction - Jo, Woohyeon; Jeong, Dasol; Jeong, Jaebum; Kim, Taegeon; Han, Seungyeon; Son, Minkyu; Kim, Yangdo; Park, Yong Ho; Jung, Hyunsung (Frontiers in Chemistry, 2021)
Nickel phosphide (Ni-P) films as a catalytic cathode for the hydrogen evolution reaction (HER) of a water splitting were fabricated by a pulse-reverse electrodeposition technique. The electrochemical behaviors for the electrodeposition of Ni-P were investigated by the characterization of peaks in a cyclic voltammogram. The composition of the electrodeposited Ni-P alloys was controlled by adjusting duty cycles of the pulse-reverse electrodeposition. The HER electrocatalytic properties of the Ni-P electrodeposits with an amorphous phase as a function of phosphorous contents existing in Ni-P were electrochemically characterized by the analysis of overpotentials, Tafel slopes and electrochemical impedance spectrometry. Additionally, the elemental Ni-embedded crystalline Ni3P was prepared by an annealing process with the amorphous Ni69P31 electrodeposit with high contents of phosphorus. The crystalline structure with Ni inclusions in the matrix of Ni3P was formed by the precipitation of excess Ni. The electrocatalytic properties of crystalline Ni3P with elemental Ni inclusions were also investigated by electrochemical characterization.